(untitled) (Proceedings of Voronezh State University. Series: Geology, 2019)
The clay deposits of the Karelian-Kola region were mainly formed due to the differentiation of detrital material transported by a glacier. This material contained a very small amount of fine particles. Its differentiation was carried out by glacial melt waters and turbid streams that originated on the advanced slopes of the fluvioglacial deltas in freshwater and marine water bodies. In the Kola region, 25 deposits and clay occurrences were found. Nineteen of them are glacial-marine formations formed during dissecting deglaciation in the gulfs. In Karelia, 71 deposits and clay occurrences have been established. The overwhelming majority of them are represented by lake-glacial clays, which were formed during both dissecting and areal deglaciation. They are concentrated, in accordance with the indicated types of deglaciation, in the environs of Lake Onega and Ladoga Basin. During frontal deglaciation, clay deposits can form only in the case of a more or less long stationary position of the glacier margin in the presence of periglacial water bodies. In Karelia, glacier clay deposits occur very seldom, marine and lake clays are found slightly more often.